RISK OF INTERNET ADDICTION AMONG ADOLESCENTS WITH ATTENTION-DEFICIT/HYPERACTIVITY DISORDER (ADHD) DURING THE COVID-19 PANDEMIC - Febria Rike Erliana; Yunias Setiawati; Henry Aoyama; I Gusti Ayu Indah Ardani (Universitas Airlangga, 2022)
Background: In lieu of COVID-19, adolescents are forced to carry out their schoolwork, social and leisure activities online. Excessive internet use can have a negative impact on psychological, social, physical, spiritual, and financial well-beings. Such phenomenon is called internet addiction, and its highest prevalence is observed among adolescents with Attention-Deficit/ Hyperactivity Disorder (ADHD). They have difficulty focusing on less attractive routines, thus they tend to have impaired daily functioning. So, internet addiction co-occuring with ADHD among adolescents warrants serious clinical attention. Purpose: This literature aims to study the risk factors and management of comorbidity of internet addiction with ADHD in adolescents. Methods: A literature review of studies investigating Internet Addiction Risk in Adolescent with Attention-Deficit/Hyperactivity Disorder (ADHD). Non-English articles were set as the exclusion criteria. Search criteria in this rewiew includes ‘internet addiction’, ‘ADHD’, ‘comorbidity’, and ‘adolescent’. Results: Adolescents with ADHD are at a heightened risk of developing internet addiction. Impulsivity, executive dysfunction, motivational dysfunction, social skill deficits and subpar attachment bonds were the primary reasons for the increased risk. Conclusion: Attempts to increase awareness on the internet addiction susceptibility among adolescents with ADHD, particularly in this COVID-19 pandemic.